Decreased levels of urinary liver-type fatty acid-binding protein after switching from tenofovir disoproxil fumarate to tenofovir alafenamide: a prospective observational study. (November 2019) - Hikasa, Shinichi; Shimabukuro, Shota; Hideta, Kyoko; Nishida, Sakurako; Higasa, Satoshi; Sawada, Akihiro; Tokugawa, Tazuko; Tanaka, Kuniyoshi; Yanai, Mina; Kimura, Takeshi
A single-center, prospective, observational study was conducted between September 2016 and August 2018 in 33 HIV-positive Japanese patients who switched antiretroviral drug regimens from tenofovir disoproxil fumarate (TDF) to tenofovir alafenamide (TAF). The study assessed changes in urinary levels of liver-type fatty acid-binding protein (L-FABP) after switching from TDF to TAF and determined the potential of renal parameters to predict improvement in estimated glomerular filtration rate (eGFR). Median urinary levels of L-FABP were found to be 2.0, 1.4, and 1.3 µg/g creatinine before, at 6 months, and at 12 months after switching to TAF, respectively. The urinary levels of L-FABP, β2 microglobulin (β2MG), and eGFR and the protein-to-creatinine ratio (PCR) were not significantly related to the annual change in eGFR after switching from TDF to TAF. Our results demonstrate a significant decrease in urinary levels of L-FABP after switching from TDF to TAF. However, neither urinary L-FABP, β2MG, PCR, nor eGFR predicted the annual change in eGFR after the change in medication.